Review on Optimised Configuration of Hybrid Solar-PV Diesel System for Off-Grid Rural Electrification. - Amanda Halim; Ahmad Fudholi; Stephen Phillips; Kamaruzzaman Sopian (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
At present, solar energy is perceived to be one of the world’s contributive energy sources. Holding characteristics such as inexhaustible and non-polluting, making it as the most prominent among renewable energy (RE) sources. The application of the solar energy has been well-developed and used for electricity generation through Photovoltaic (PV) as the harvesting medium. PV cells convert heat from the sun directly into the electricity to power up the electric loads. Solar PV system is commonly built in a rural area where it cannot be powered up by the utility grid due to location constrains. In order to avoid the electricity fluctuation because of unsteady amount of solar radiation, PV solar hybrid is the efficient solution for rural electrifications. This paper presents a review on optimised Hybrid Solar-PV Diesel system configurations installed and used to power up off grid settlements at various locations worldwide.